Erasmus's Ideal Wise Christian: A Reading of De Contemptu Mundi (Minerva, 2019)
For Erasmus the ideal sophós is the life of the Christian humanist, inspired by Jerome of Stridon. The Christian intellectual must proclaim and express the truth of Christ with his own customs and with his writings. This attitude generates the human salvation, which does not arise from outerappearance-based monasticism, but from inner life and faith.
Keywords: Ethics; Erasmism; Religion; Interiority; Salvation